Lyapunov-Based Adaptive State of Charge and State of Health Estimation for Lithium-Ion Batteries - Chaoui, Hicham; Golbon, Navid; Hmouz, Imad; Souissi, Ridha; Tahar, Sofiene (IEEE transactions on industrial electronics (1982), 2015)
This paper presents an adaptive state of charge (SOC) and state of health (SOH) estimation technique for lithium-ion batteries. The adaptive strategy estimates online parameters of the battery model using a Lyapunov-based adaptation law. Therefore, the adaptive observer stability is guaranteed by Lyapunov's direct method. Since no a priori knowledge of battery parameters is required, accurate estimation is still achieved, although parameters change due to aging or other factors. Unlike other estimation strategies, only battery terminal voltage and current measurements are required. Simulation and experimental results highlight the high SOC and SOH accuracy estimation of the proposed technique.